Multi‐port‐driven birdcage coil for multiple‐mouse MR imaging at 7 T. Issue 6 (10th May 2016) - Heo, Phil; Seo, Jeung‐Hoon; Han, Sang‐Doc; Ryu, Yeunchul; Byun, Jong‐Deok; Kim, Kyoung‐Nam; Lee, Jung Hee
Summary: In ultra‐high field (UHF) imaging environments, it has been demonstrated that multiple‐mouse magnetic resonance imaging (MM‐MRI) is dependent on key factors such as the radiofrequency (RF) coil hardware, imaging protocol, and experimental setup for obtaining high‐resolution MR images. A key aspect is the RF coil, and a number of MM‐MRI studies have investigated the application of single‐channel RF transmit (Tx)/receive (Rx) coils or multi‐channel phased array (PA) coil configurations under a single gradient coil set. However, despite applying a variety of RF coils, Tx (|B1 + |)‐field inhomogeneity still remains a major problem due to the relative shortening of the effective RF wavelength in the UHF environment. To address this issue, we propose a relatively smaller size of individual Tx‐only coils in a multiple birdcage (MBC) coil for MM‐MRI to image up to three mice. We use electromagnetic (EM) simulations in the finite‐difference time‐domain (FDTD) environment to obtain the |B1 |‐field distribution. Our results clearly show that the single birdcage (SBC) high‐pass filter (HPF) configuration, which is referred to as the SBCHPF, under the absence of an RF shield exhibits a high |B1 |‐field intensity in comparison with other coil configurations such as the low‐pass filter (LPF) and band‐pass filter (BPF) configurations. In a 7‐T MRI experiment, the signal‐to‐noise ratio (SNR) map of the SBCHPF configuration shows the highest coil performance compared to other coil configurations. The MBCHPF coil, which is comprised of a triple‐SBCHPF configuration combined with additional decoupling techniques, is developed for simultaneous image acquisition of three mice. SCANNING 38:747–756, 2016. © 2016 Wiley Periodicals, Inc.